Profiling and framing structures for pervasive information systems development - Fernandes, José Eduardo Moreira (2012)
Pervasive computing is a research field of computing technology that aims to achieve a new computing paradigm. Software engineering has been, since its existence, subject of research and improvement in several areas of interest. Model-Based/Driven Development (MDD) constitutes an approach to software design and development that potentially contributes to: concepts closer to domain and reduction of semantic gaps; automation and less sensitivity to technological changes; capture of expert knowledge and reuse. This paper presents a profiling and framing structure approach for the development of Pervasive Information Systems (PIS). This profiling and framing structure allows the organization of the functionality that can be assigned to computational devices in a system and of the corresponding development structures and models, being. The proposed approach enables a structural approach to PIS development. The paper also presents a case study that allowed demonstrating the applicability of the approach.